PREVENTIVE STRATEGIES FOR ISCHEMIC STROKE IN STENOTIC LESIONS OF CEREBRAL ARTERIES (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Ischemic stroke remains one of the leading causes of mortality and long-term disability worldwide. Among the most significant risk factors for its development are stenotic lesions of the carotid arteries caused by atherosclerosis or structural vascular abnormalities. The present prospective study evaluated predictors of ischemic stroke in patients with dyscirculatory encephalopathy and carotid artery pathology of different etiologies. The study included 80 patients who were followed for 12 months. Participants were divided into two groups: Group I (n = 50) consisted of patients with transient ischemic attacks associated with atherosclerotic carotid artery stenosis, whereas Group II (n = 30) included individuals with structural carotid artery abnormalities such as kinking and coiling. Neurological examinations, clinical assessments, duplex ultrasonography of brachiocephalic arteries, and the ABCD3 risk scoring system were used to evaluate stroke risk and vascular status. The findings demonstrated that patients with atherosclerotic carotid stenosis had a significantly higher risk of ischemic stroke compared with individuals with structural arterial deformities. Duplex ultrasound proved to be a highly effective diagnostic tool for detecting hemodynamic disturbances and vascular morphology changes. The results highlight the importance of early vascular screening and risk assessment in preventing ischemic stroke.
Keywords: Ischemic stroke, carotid stenosis, duplex ultrasound, arterial kinking, arterial coiling, ABCD3 risk score, cerebrovascular disease.